SECOND FOREIGN LANGUAGE IN THE SYSTEM OF MULTILINGUAL EDUCATION: METACOGNITIVE STRATEGY OF COMPARISON - L.M. Malykh (Многоязычие в образовательном пространстве)
The paper reviews a teaching aid written by a team of authors «Second foreign language in the system of multilingual education» (Izhevsk, 2023). The teaching aid tackles burning issues of studying several languages simultaneously by university students. The aim of the paper is to introduce the book to the reader and draw special attention to one of the most important metacognitive strategies of second foreign language acquisition - that is comparison. From a methodological point of view, the paper is descriptive with some elements of analysis. Key terms and notions of modern multilingual education are given special attention to. They are: multilingual personality, artificial trilingualism, the process of costudying languages, metalinguistic consciousness, the role of the native tongue in costudying languages, the typology of contrastive exercises. Special attention is given to the notion of multilingual communicative competence which is not a mere sum of different languages in a person’s head, but a combined configuration of skills based on the languages a person has acquired.